Digitalization of learning media: A comparative study on metacognitive ability, learning interest, and activeness in Islamic High School 2 Banyumas Excellent Class - Perwita, Dyah; Zulfa, Zulfa (Jurnal Inovasi Teknologi Pendidikan, 2025)
The growing use of digital learning media calls for a deeper investigation into its effects on students' psychological aspects, particularly metacognitive ability, learning interest, and activeness. It aims to compare students’ metacognitive ability, learning interest, and activeness before and after implementing digital learning media. This study focuses on 80 10th-grade students in the Excellent Class at Islamic High School (MAN) 2 Banyumas during the 2023/2024 academic year. Using a descriptive comparative quantitative approach with a survey method, data were collected through non-probability sampling with a saturation (census) technique. The results show significant differences in all three aspects after the implementation. Specifically, students' metacognitive ability improved by 19%, learning interest by 37%, and learning activeness by 31%. These findings confirm that digital learning media have a positive impact on students’ learning experiences. It enhances their ability to monitor their learning, increases their engagement, and encourages more active class participation. The results highlight the value of digital tools in supporting modern education. However, further research is needed to identify specific causal factors contributing to these improvements, such as interface usability and the integration of interactive learning features. Additionally, long-term studies are recommended to examine the sustainability of these benefits over time and how digital media can be continually optimized to support student development.